Anti-Vaxxers, Politicization of Science, and the Need for Trust in Pandemic Response. Issue 10 (2nd October 2020) - May, Thomas
ABSTRACT: The effectiveness of the next stages of pandemic response will require widespread compliance with vaccination recommendations once effective vaccines become available. Challenges to routine childhood immunization from anti-vaccination activists illustrate the importance of trust for achieving compliance. Unfortunately, we live in a time of political polarization that results in competing distortion of scientific study results. Science should take care to maintain objectivity, or we will lose the common ground of shared facts upon which progress depends.